Increasing the Effectiveness and Efficiency of Local MSME Consignment Cooperation with the Portal Vendor System - Fredy Rizaldi; Agus Munandar (Publikasi Indonesia, 2024)
MSMEs have an important role in the Indonesian economy, but they face challenges in adapting to the digital era and establishing effective collaborations with retail companies. This study aims to develop and evaluate a vendor portal system that can overcome this challenge by increasing the effectiveness and efficiency of consignment cooperation between local MSMEs and retail companies. Using a qualitative descriptive method, this study analyzes the impact of the implementation of the vendor portal system on the consignment business process, including operational efficiency, transparency, and collaboration between the two parties. The results show that the vendor portal system has succeeded in improving operational efficiency, providing real-time transparency of sales and inventory data, and facilitating better communication between MSMEs and retail companies. In addition, this system also supports the government's program in encouraging MSMEs to